Numerical investigation on heat transfer performance and flow characteristics in a rectangular air cooling channel (AR = 2) with ridged dimples. (April 2017) - Zheng, Lu; Xie, Yonghui; Zhang, Di
Graphical abstract: Highlights: A numerical study on effect of ridged dimples on heat transfer is conducted. A comparative analysis between ridged dimple and spherical dimple is conducted. The effects of extending ratio and Reynolds number are considered. The influence on entropy generation and wall temperature uniformity is studied. Abstract: As an innovative type of structure, ridged dimples exhibit great potential for heat transfer enhancement. In this study, the effects of ridged dimples on heat transfer, flow characteristics and entropy generation in a rectangular air cooling channel with aspect ratio of 2:1 are numerically investigated. A comparative and comprehensive analysis is accomplished, considering the influences of extending ratio r and Reynolds number Re, as well as a comparison with the results of spherical dimple case. It is shown that heat transfer is further enhanced when ridged dimples are employed compared with spherical dimple case, and the effect is markedly promoted when r increases. The spherical dimple primarily affects the dimpled wall, while the influence of ridged dimple on heat transfer enhancement is mainly reflected on the side walls and top wall. In addition, the areas of the high temperature regions at the side boundaries of all walls significantly decrease with an increasing r . Besides, the overall turbulent kinetic energy TKE in the domain of spherical dimple case is in a relatively low level. When ridged dimples are adopted, a considerably large area of high TKE is detected in the domain above the dimpled wall. And the proportion of the high TKE region in the domain rises with the increase in r . In ridged dimple cases, the low TKE regions found in spherical dimple case at the side boundaries are not detected. The overall TKE level in ridged dimple case is higher than that of spherical dimple case. Furthermore, the average heat transfer entropy generation rate and average total entropy generation rate are prominently reduced with the employment of ridged dimples, while a slight increase in average friction entropy generation rate is detected. The employment of ridged dimple significantly reduces the maximum wall temperature and distinctly improves the wall temperature uniformity, with a further enhanced effect when r ascends, greatly beneficial for safe and stable operations of engineering devices.